Taxonomic reassessment of Rehderodendron gongshanense (Styracaceae) based on herbarium specimens and field observations - Zhao, Wan-Yi; Fritsch, Peter W.; Fan, Qiang; Liao, Wen-Bo (Phytotaxa, 2020)
Since its publication in 1988, Rehderodendron gongshanense (Styracaceae) has been considered endemic to Gongshan County, Yunnan Province, China and northern Myanmar. Based on morphological data from detailed field observations and examination of herbarium specimens, we demonstrate that R. gongshanense is actually a synonym of R. microcarpum, a species until now neglected taxonomically. We provide an updated description of R. microcarpum that accommodates the variation in the newly expanded concept of the species, along with comments on distribution and ecology, conservation status, specimens cited, and images of the living plants.